Energy Sharing and Energy Feedback: Affective and Behavioral Reactions to Communal Energy Displays - Leygue, Caroline; Ferguson, Eamonn; Skatova, Anya; Spence, Alexa (Frontiers in Energy Research, 2014)
Smart meters and energy displays are being rolled out in many countries to help individuals monitor and reduce their energy usage. However, to date, there is little in depth understanding of how they may change behavior. While there is currently a great deal of technical research into developing smart metering, little research has been conducted on how this affects the energy user. This research addresses this gap and explores the user perspective of energy displays when energy is considered as a shared resource. We report an online experiment conducted across the UK examining affective and behavioral responses to energy sharing situations incorporating different types of energy displays. Reactions differed depending on the type of display. In a situation where one person used more than their fair share of energy, displays showing the average amount of usage in the house were associated with feelings of guilt and fear and a decrease in intention to use energy. Displays that identified the person who overused the resource were associated with anger, and direct sanction intentions on those who were overusing energy. Findings are discussed in terms of the smart meter rollout and the potential utility of detailed energy monitoring technologies for behavior change.